Reforma Agrária: o incômodo diálogo - Paulino, Eliane Tomiasi (Universidade de São Paulo. Faculdade de Filosofia, Letras e Ciências Humanas, 2011)
In the agricultural modernization context a discourse was oriented to the international development efforts aimed at poor countries with hunger problems. Since then, the cyclical weakness has been used to justify the minimum hunger decrease with the promises that new technical solutions will solve them, but in the next cycle, tend to reinforce the same vulnerabilities. The thesis defended here is that this issue is not a temporary problem, according say governments and contemporary diplomacy, but rather a structural problem of the accumulation model, so society and environmental require new solutions, due to the fact the results no more justify to maintain the strategies that have been implemented for almost half a century without success. To reflect about limits and alternatives to agriculture, the environment and society we propose an analysis of the hegemonic discourses contradictions and practices from social classes.